Participation can make a difference to be competitive in sports: A systematic review on the relation between complex motor development and self-controlled learning settings - Jaitner, D.; Mess, F. (International Journal of Sports Science & Coaching, 2019)
The purpose of the study was to provide an empirically based argument that grounds the relation between potentials of athletic performance and participatory settings within the autonomous inner logic of competitive sports. Therefore, the present paper systematically reviewed the empirical evidence of the association between complex motor learning and performance, and self-controlled practice conditions. Six electronic databases, reference lists and citations of full-text articles were searched for English and German language peer-reviewed articles. The search string multiply combined different terms relating to motor learning AND self-control. Two reviewers evaluated the full-text articles and critically appraised the included studies. Thirty-one studies with 1273 participants met the inclusion criteria. The vast majority of the studies reported significant learning advantages for experimental groups under self-controlled practice conditions compared to experimenter-imposed yoked groups. No study showed adverse effects. Thereby, the effects of self-controlled practice conditions have been shown to be relatively generalised to a variety of participatory variables and target groups. Advantages in accuracy, form and performance were more frequently reported than advantages in consistency. Despite increasing research efforts, the explanatory underpinnings behind the learning benefits remain debatable. The evidence indicates that complex motor learning and motor performance are typically enhanced when learners are given the opportunity to take part in decisions and therefore presents profitable implications for coaches and anyone responsible in competitive sports. However, in order to become a professional effective argument, the social context and the status of reasoning in changing habits need to be considered.